Descriptive epidemiology of varicella based on national surveillance data before and after the introduction of routine varicella vaccination with two doses in Japan, 2000–2017. Issue 40 (25th September 2018) - Morino, Saeko; Tanaka-Taya, Keiko; Satoh, Hiroshi; Arai, Satoru; Takahashi, Takuri; Sunagawa, Tomimasa; Oishi, Kazunori
Highlights: Routine two-dose varicella vaccine was introduced in Japan in October 2014. Varicella case number per sentinel decreased by 88% in young children in 2017. A decrease in the number of hospitalized cases aged <5 years was found after 2015. Major suspected transmission sites were household, school, workplace and hospital. With self-report, 30% of varicella cases were infected from a herpes zoster case. Abstract: Routine childhood immunization using two doses of the varicella vaccine was introduced in Japan in October 2014. In this study, we analyzed the data extracted from national varicella surveillance, including pediatric sentinel surveillance from 2000 to 2017 and hospitalized varicella surveillance from the 38th week of 2014 to the 37th week of 2017. Compared with the 2000–2011 baseline data, the number of varicella cases per sentinel decreased substantially by 76.6% overall and by 88.2% among children aged 1–4 years in 2017. Of 997 hospitalized patients, we found a decreasing trend in the number of cases among children aged <5 years. We also found a decreasing trend in the number of cases with complications among children aged 1–4 years. Data on the self-reported transmission sites in 35.5% (354/997) of the hospitalized varicella patients showed that transmission of varicella zoster virus (VZV) occurred frequently in household, at school for young children, in the workplace for adults, and at hospital for all age groups. Data from 29.0% (289/997) of the hospitalized patients with a self-reported source of infection showed that transmission of VZV occurred from a patient with herpes zoster (HZ) in 30.4% (88/289) of cases. Our data demonstrate a substantial decrease in the number of varicella cases in young children following introduction of routine childhood vaccination program with two-dose varicella vaccination in Japan. These data highlight the unique aspects of transmission sites across age groups and the important role of HZ cases in disease circulation.